2019
DOI: 10.15644/asc53/2/8
|View full text |Cite
|
Sign up to set email alerts
|

A Color Stability Comparison of Conventional and CAD/CAM Polymethyl Methacrylate Denture Base Materials

Abstract: Objective The aim of this study was to evaluate the color stability of a heat polymerized resin, an auto-polymerizing resin, a urethane dimethacrylate resin and a CAD/CAM PMMA block resin stored in different storage media. Materials and methods 60 disc-shaped specimens (15×2 mm) were fabricated for each group. A total of 240 disc-shaped specimens were thermal-cycled for 5,000 cycles. Then specimens were randomized into 4 groups (n= 15) according to storage media: coffee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 38 publications
2
46
2
5
Order By: Relevance
“…According to the literature, both of them belong to materials having the greatest influence on the PMMA colour. 15 Considerably higher ΔE values were observed for samples coloured with red wine. In comparison to pure PMMA, smaller concentrations of nanocomposites behaved similarly or were discoloured to a slightly greater extent.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…According to the literature, both of them belong to materials having the greatest influence on the PMMA colour. 15 Considerably higher ΔE values were observed for samples coloured with red wine. In comparison to pure PMMA, smaller concentrations of nanocomposites behaved similarly or were discoloured to a slightly greater extent.…”
Section: Discussionmentioning
confidence: 96%
“…Oba uznawane w piśmiennictwie jako jedne z najbardziej oddziałujących na zmianę koloru PMMA. 15 Zaobserwowano znacznie wyższe wartości ΔE dla próbek barwionych czerwonym winem. W porównaniu do czystego PMMA mniejsze stężenia nanokompozytów zachowywały się podobnie lub ulegały niewiele większemu przebarwieniu.…”
Section: Discussionunclassified
“…Coffee provoked the greatest TP changes, followed by red wine and artificial aging, which showed to be alike. It was reported that yellow stain molecules with low polarity present in coffee are attracted by the polymer network leading to greater color changes ( 31 ) and that coffee and wine affect translucency and color significantly ( 12 , 32 ). The TP 00 mean values and TP 00 retention decreased from T0-T1 to T0-T2.…”
Section: Discussionmentioning
confidence: 99%
“…Coffee provoked the greatest TP changes, followed by red wine and artificial aging, which showed to be alike. It was reported that yellow stain molecules with low polarity present in coffee are attracted by the polymer network leading to greater color changes (31) and that coffee and wine affect translucency and color significantly (12,32). The TP 00 mean values and TP 00 retention decreased from T0-T1 to T0-T2.…”
Section: Raspravamentioning
confidence: 97%
“…Kava je prouzročila najveće promjene TP-a, a sličnima su se pokazali crveno vino i umjetno starenje. Navodi se da polimerna mreža privlači molekule žutoga pigmenta s niskim polaritetom u kavi, što rezultira većim promjenama boje (31) te da kava i vino značajno utječu na translucenciju i boju (12,32). Prosječne vrijednosti TP 00 i zadržavanja TP 00 smanjile su se s T0 -T1 na T0 -T2.…”
Section: Raspravaunclassified